The Influence of Teamwork and Person-Environment Fit on Employe Turnover Intention with Organizational Citizenship Behavior as A Mediating Variable (Study Case on Sinar Mas Land Customer Care) - Sekarsari, Dewanti Putri; Lo, Singmin Johanes (Dinasti Publisher, 2025)
The purpose of this study is to examine how Teamwork and Person-Environment Fit influence Turnover Intention mediated by Organisational Citizenship Behavior (OCB) in Sinar Mas Land particularly customer care division. Data was obtained by distributing a closed questionnaire filled up by 117 participnats, and the data processing was then conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) with a software SmartPLS 3.0. The result shows that Teamwork does not negatively affect Turnover Intention but positively contribute to OCB. Meanwhile, Person-Environment Fit has a negatif effect toward Turnover Intention and a positif effect toward OCB. There is a reduction in the intention of turning over influenced by OCB. Moreover, OCB also functions as a mediator between Person- Teamwork and Person-Environment Fit toward Turnover Intention. These findings urge to strengthen Teamwork and employee-environment in order to enhance the development of OCB in Sinar Mas Land Customer Care